2021
DOI: 10.3389/fpsyg.2021.695468
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Philanthropic CSR in Digital China: Unified View of Prosocial and Pro-environmental Practices

Abstract: In recent decades, China has transformed from a conventional society into a digitally competitive nation. From an economic perspective, embedded corporate social responsibility (CSR) is gaining a new height where gamified charity is a trendy approach. By adopting the norm activation model from the point of view of the stimulus–organism–response framework, this research theoretically conceptualized the role of the mobile application environment (including telepresence, functional transparency, and accessibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 134 publications
(164 reference statements)
0
7
0
Order By: Relevance
“…In addition, the previous literature suggested that hedonic motivation influenced consumer behavior through virtual CSR 76 . Virtual CSR initiatives can increase consumers' awareness and knowledge of companies' environmental and social initiatives, reinforcing their environmental attitudes and behaviors 77 .…”
Section: Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 99%
“…In addition, the previous literature suggested that hedonic motivation influenced consumer behavior through virtual CSR 76 . Virtual CSR initiatives can increase consumers' awareness and knowledge of companies' environmental and social initiatives, reinforcing their environmental attitudes and behaviors 77 .…”
Section: Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 99%
“…This allows us to support social progress, increasing environmental values with each responsible purchase and stimulating further responsible purchases. The purchase of products from environmentally responsible suppliers can become a social trend, increasing the supply and demand of these products, as well as keeping an equilibrium (fair) price for it (Ye et al, 2021;Yin et al, 2021).…”
Section: Rethinking Of Environmental Csr From the Perspective Of Stak...mentioning
confidence: 99%
“…However, little research has examined relevant outcomes and psychological mechanisms within a single framework. To maximize the positive effect of CSR in a digital context, several studies have advocated for more comprehensive research into the initial conditions and occurrence mechanisms governing sustained customer engagement [1,13]. This study responds to these calls by proposing a moderated mediation model for the relationship between customer engagement and sustainable customer outcomes.…”
Section: Introductionmentioning
confidence: 98%
“…Companies have implemented corporate social responsibility (CSR) practices in order to achieve sustainable performance while addressing their social and ecological concerns in a balanced manner [1]. CSR refers to corporates voluntarily incorporating social, environment and economic welfare into their business activities and represents the relationship between corporates and their stakeholders [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation